Agustín Víctor Casasola's Engagement with Positivism and Spectacle in his Imagining of Mexico City During the Late Porfiriato, 1900–10. - White, Russell (Hispanic Research Journal, 2019)
Photography would play a crucial role in documenting the changes that the inhabitants of Mexico City experienced at the end of the nineteenth and beginning of the twentieth century. The first decade of the twentieth century saw the emergence of photojournalism in Mexico. Newspapers and magazines started to use photographs to authenticate their stories; a strategy that reflected an epistemology that saw in the photograph an inherent truth. Among the most important photojournalists working during this period was Agustín Víctor Casasola. Casasola was a taker and a collector of photographs. Although often seen as the photographer of the Mexican Revolution, Casasola also documented the latter years of the Porfiriato whilst working for El Imparcial, among others. This article explores Casasola's work during the period 1900–10, and considers the way in which Casasola's photographs deployed positivist tropes and spectacle to establish a visual regime for Porfirian modernity. This regime sought to index industrial progress and the development of Mexico City as a modern space.